Antenatal Exposure to Ambient Fine Particulate Matter Pollution and Amoxicillin Dispensing in Infants: National Birth Cohort Study in Scotland - Akaraci, Selin; Rammah, Amal; Hart, Caroline; De Stavola, Bianca; Macfarlane, Alison; Dibben, Chris; Taylor, Jonathan; Wijlaars, Linda; Clemens, Tom; Cunningham, Steve; Hardelid, Pia (International Journal of Population Data Science, 2025)
Background Exposure to ambient air pollution has been linked to increased risk of respiratory infections in children, which may require antibiotics. However, the impact of prenatal exposure to air pollution on antibiotic use in infancy remains unexplored. Methods We linked maternal postcode at delivery to modelled annual fine particulate matter ambient air pollution (PM2.5) concentration data and national birth and community pharmacy dispensing data for all singleton children born in Scotland from 2009 to 2018. The association between PM2.5 exposure and amoxicillin and phenoxymethylpenicillin dispensing for children under one year old, was estimated using logistic regression (odds ratio (OR) for ever dispensed) and negative binomial regression models (incidence rate ratio (IRR) for total dispensed). Models were adjusted for birth year, season, infant sex, maternal age, and smoking during pregnancy. Results Antenatal PM2.5 concentrations for 421,289 children ranged from 2.9 to 16.5 µg/m3. The amoxicillin dispensing rate was 450/1000 child-years during year 1 (95% CI: 448, 451); 32.4% of children were dispensed at least one dose. A unit and interquartile range (IQR) increase in PM2.5 was associated with a 4% (OR:1.04, 95% CI: 1.03-1.05) and 8% (OR:1.08, 95% CI:1.06-1.10) increase in odds of amoxicillin dispensing and a 4% (IRR: 1.04, 95% CI: 1.03-1.04) and 7% (IRR:1.07, 95% CI:1.06-1.08) increase in dispensing rates. For phenoxymethylpenicillin, the dispensing rate was 343/1000 child-years (95% CI: 384, 396), 3% of children received at least one dose. A unit increase in PM2.5 was associated with a 6% increase in odds of dispensing (OR:1.06, 95% CI:1.04-1.08), and an IQR increase with a 13% increase (OR:1.13, 95% CI:1.08-1.17). Similarly, negative binomial regression showed a 9% (IRR:1.09, 95%CI:1.07-1.11) and 18% (IRR:1.18, 95%CI:1.14-1.23) increase with unit and IQR increases in PM2.5. Conclusion Antenatal exposure to PM2.5 was associated with an increased likelihood and frequency of amoxicillin and phenoxymethylpenicillin dispensing during infancy, reflecting its potential impact on early life respiratory health. Targeted interventions to improve air quality during pregnancy may reduce the burden of antibiotic use.